INTELLIGENT INFORMATION TECHNOLOGY FOR ORGANIZING SWIMMING COMPETITIONS (Physical Culture and Sport: Scientific Perspective, 2022)
The development and implementation of new competitive information technologies in various spheres of human activity in order to reduce the share of physical labor and minimize the influence of the human factor on decision-making is the main goal of the development of the information society in Ukraine.Even more important is the development of multidisciplinary sports software, which is developed at the junction of sports and other subject areas - for example, the field of competition organization. The combination of the sports industry and new information technologies makes it possible to make the organization of sports events more efficient.Throughout the existence of sports complexes of swimming pools, competition judges independently dealt with organizational issues, such as: creating a single database of participants, rating, protocol, formation of swims, sorting of participants by different categories, calculation of FINA points, checking for obtaining a new category, etc.The development and implementation of the latest competitive information technologies in the field of organizing swimming competitions will significantly save time and increase the productivity of judges and employees organizing competitions.To date, the judges of the competition independently dealt with organizational issues, such as: creating a single database of participants, ranking, protocol, formation of swims, sorting participants by different categories, calculating FINA points, checking for a new category and more. The presented intelligent information technology for the organization of swimming competitions simplifies the process of forming different types of competition protocols, which saves a lot of time and increases the productivity of judges and employees who organize swimming competitions. The rules for the formation of protocols, method and structural scheme of intelligent information technology for the organization of swimming competitions were first developed by the authors.
Keywords: protocols of swimming competitions; intelligent information technology; semantic analysis of natural language